Estilos de crianza y la personalidad en adolescentes. - Jaramillo Paladinez, José Luis (2018)
The present research seeks to determine the relationship between parenting styles and personality characteristics in adolescents that are expressed through behaviors and behaviors, considering that are acquired through the norms, values, roles, rules, expressions of affection, communicative, and family dynamics that keep these families. The work is based on the Cognitive-behavioral approach that explain the behavior and the general conduct of individuals and the environment in which they interact, and form part of the development of identity; the categories of analysis for the study were, parenting styles and personality of adolescents. The study was conducted with four teenagers, two boys and two girls, ranging between 14 to 15 years of age and their families have a nuclear structure, these families live in the neighborhood Providence of the city of Machala. The research is governed under the mixed method qualitative-quantitative, the design is descriptive-narrative that allows to know the personal and family history of adolescents, and finally the biographical method for understanding the story of the study subjects, their history of personal, family and social life. The scope was of a descriptive-interpretative to characterize and interpret the family interaction and behaviors that are linked to education exercised by the parents.